Development of Web-Based English Proficiency Test Model for EFL Classroom - Hasan Ayuba; Aleeyah Masae (Al-Lisan: Jurnal Bahasa, 2022)
The digital transformation of higher education institutions is a critical concern that several stakeholders in education must address; however, abilities to apply ICT in all spheres of life are still evolving, most notably Web-based tests to assess students' English proficiency. This research aims to produce a Web-Based English proficiency test for the English Education Study Program in State Institute of Islamic Studies (IAIN) Sultan Amai Gorontalo. The type of this research was Research and Development (R&D). The researcher modified Borg and Gall's development research model, which consisted of five steps:(1) evaluation of material and media experts, (2) one-on-one trial, (3) small group trial, (4) field trial, and (5) the final product.The evaluation was conducted by a media and material expert. The trial subjects consisted of 40 students: 12 students of one-to-one trial, 20 students of small group trial, and 40 students of field trial (including those in one-to-one and small group trial students). The data collection instrumentsused was an evaluation sheet for material expert, media expert, and a questionnaire for students involved in the display and the web system aspects. The data were analyzed by using descriptive quantitative, and qualitative techniques. The research result revealed that the Web-Based Test of English proficiency for English Program,developed determined by the media expert, indicated that the web display aspect assessed “good” (4,07). Meanwhile, the evaluation result from media expertsshowed from the system aspect considered “good” (4,10). The final product of this research was a web-based test for English Proficiency with the domain address www.eptestee.or.id.